Efficacy of Green Roof Technology in Colder Climates - Corden, Yancey (Earth Common Journal, 2011)
Green roof technology has been used within Canada as early as the first French settlers (1600) in the provinces of Nova Scotia and Newfoundland for necessity and survival in the Canadian wilderness. As home construction became more modernized, green roof technology was replaced by conventional roofing on houses and businesses. However, with the increased awareness of sustainable practices and environmental conservation, several European companies introduced new green roof technologies in the 1980s that began the movement of using this technology. While this technology has primarily been used in mild climates throughout Canada (Vancouver, British Columbia), little has been examined and researched regarding the use of green roof technology in colder and more severe climates within Canada. In his final year to complete his Bachelor Degree in Technology at the Northern Alberta Institute of Technology, Yancey Corden conducted research on the efficacy of green roof technology in Edmonton, Alberta capital region’s cold and severe climatic conditions. The results suggested that native plants to the region are most successful when used in green roof technology.